Digital Innovation in Islamic Character Education: An H5P Media Development Analysis at Elementary School - Mudlofar, Muhammad; Sahlan, Moh; Sutomo, Moh (Program Studi PGMI, 2025)
Islamic Religious Education and Character Development plays a vital role in shaping students’ moral foundations. Traditional teaching methods often fall short in fostering engagement and deep internalization of values. This study aims to analyze the development and implementation of H5P-based interactive media in Islamic Education at SDN 1 Sukorejo.This qualitative research employed a case study approach. Data were collected through classroom observation, in-depth interviews with teachers and students, and documentation of learning artifacts. The data were analyzed using descriptive qualitative methods with triangulation of sources and techniques.The findings indicate that H5P interactive media including interactive videos, drag-and-drop tasks, and branching scenarios enhanced student engagement, supported moral reflection, and facilitated internalization of core Islamic values such as honesty and empathy. Teachers responded positively, although technical limitations and time constraints were noted during media development. Offline implementation proved effective in low-infrastructure settings.These results align with recent studies demonstrating the effectiveness of digital media in supporting Islamic character education. H5P emerges as an adaptable and engaging tool suitable for primary education, provided that teacher training, linguistic adaptation, and institutional support are in place. It represents a viable solution for modernizing Islamic moral education in the digital era.